A new species of the subterranean amphipod genus Stygobromus (Amphipoda: Crangonyctidae) from two caves and a spring in western Maryland, USA with additional records of undescribed species from groundwater habitats in central Maryland - Holsinger, John R.; Ansell, Lynnette (Zootaxa, 2014)
A new species of the subterranean amphipod genus Stygobromus is described from two caves and a small spring on the Appalachian Plateau in Garrett County in western Maryland, USA. The description of this species brings to six the total number of species in the genus Stygobromus from the state of Maryland. The other five species are recorded from shallow groundwater habitats (e.g., seeps and springs) in the eastern and southeastern parts of the state. In addition, at least four new species of Stygobromus from central Maryland are recognized but remain undescribed to date.